(untitled) (Academicia Globe: Inderscience Research, 2021)
The kidney is considered one of the important organs in the human body and is involved in many processes that take place in the body. Various pathologies that occur in the kidneys, in which they perform physiological functions, give clinical signs late on account of the abundance of clots Reserve, which is considered a histological functional unit, and diseases, in which cases of late detection or pronounced jaundice in the kidneys is often encountered. To this end, the pathogistological study of the diseased kidneys in the materials obtained in the process of autopsy, conducted in patients who died from various diseases. The purpose of the study was to formulate data on indications of kidney pathologies.